Procesos lectores en estudiantes de dos turnos del 2° grado de primaria de una institución educativa estatal - Pachacútec - Guevara Álvarez, Milady (2011)
The present investigation has as aim compare the different psychological processes of the reading between the students of two shifts of the second degree of primary education of Pachacútec's educational state institution. There were selected a sample of 33 children and girls of the shift tomorrow and 27 children and girls of the shift late of a socioeconomic low level to which there was applied the Battery of Evaluation of the Reading Processes (PROLEC) elaborated for F. Cuetos , B. Rodríguez and E. Ruano (2000). A profile of performance was elaborated in each of the processes of the reading. To find the differences of the performance of the pupils of the shift tomorrow opposite to those of the shift late there was in use the statistician Or of Mann Whitney. One found a better performance in all the processes of the reading in the pupils of the shift tomorrow opposite to those of the shift late. When the comparison was realized bearing in mind each of the sub test one found differences in favour of the shift tomorrow except in the reading of words and the grammatical structures. One recommends to strengthen the deficit areas specially in the pupils of the shift late.